Self-representation, Violence and Periphery in Capão Pecado - Pereira da Silva, Keury Carolaine; Pires de Assis, Emanoel Cesar (Lingüística y Literatura, 2020)
This research analyzed how the search for self-representation in literature claims the presence of peripheral groups and differs in the specificities of language and aesthetics, such as the case of violence in the work Capão Pecado, by Ferréz. Therefore, the considerations about this theme were expressed, from the perspective of those who practice and are the target of this impetus. In order to reach the scope of this research, some theorizations were considered. Finally, it is considered that the book suggests a reflection about the common perceptions of favelas and their residents, by providing new views of them.